2018
DOI: 10.1111/ner.12706
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Multi-Scale Computational Model for Non-Invasive Cervical Vagus Nerve Stimulation

Abstract: These findings indicate that realistic and precise modeling at both macroscopic and mesoscopic scales are needed for quantitative predictions of vagus nerve activation. Based on this approach, we predict conventional cervical nVNS protocols can activate A- and B- but not C-fibers. Our state-of-the-art implementation across scales is equally valuable for models of spinal cord stimulation, cortex/deep brain stimulation, and other peripheral/cranial nerve models.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(54 citation statements)
references
References 94 publications
(116 reference statements)
2
52
0
Order By: Relevance
“…Due to the clinical nature of this study, the target engagement of the cervical vagus nerve could not be validated directly. This study relies on previous literature that reported the ability to reach the vagal afferents using tcVNS [46,47]. We replicated the stimulation application reported in Ref.…”
Section: Limitationsmentioning
confidence: 53%
See 1 more Smart Citation
“…Due to the clinical nature of this study, the target engagement of the cervical vagus nerve could not be validated directly. This study relies on previous literature that reported the ability to reach the vagal afferents using tcVNS [46,47]. We replicated the stimulation application reported in Ref.…”
Section: Limitationsmentioning
confidence: 53%
“…While fewer studies exist focused on tcVNS, several important results have been demonstrated. Imaging studies noted vagal afferents are accessible with tcVNS [46] and, recently, a multi-scale image-derived model of tcVNS was developed predicting the fiber activation due to tcVNS [47]. The downstream effects were observed in serum cytokines, chemokines, and cardiac vagal tone [48,49].…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, we did not directly corroborate the successful stimulation of the vagus nerve. As nVNS mainly stimulates afferent vagal fibers, 55 heart rates are not useful to confirm successful nVNS. 16,56 However, previous results strongly suggest that cervical nVNS indeed activates vagal afferents.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings suggest a central action on the specific cortical areas generating the late vertex complex and especially the P2 wave. This effect was obtained with a not nociceptive stimulation, as the conventional cervical nVNS protocols cannot activate a-delta or C-fibers ( Mourdoukoutas et al, 2018 ). These fibers input could thus interfere with the a-delta afferent volley elicited by laser stimulation, by inhibiting late responses at cortical level.…”
Section: Discussionmentioning
confidence: 99%